Distributed Control of the Center of Mass of a Modular Robot - Moll, Mark; Will, Peter; Krivokon, Maks; Shen, Wei-min (2006 IEEE/RSJ International Conference on Intelligent Robots and Systems, 2006)
We present a distributed controller for the center of mass of a modular robot. This is useful for locomotion of a modular robot over uneven and unknown terrain. By controlling the center of mass, a robot can prevent itself from falling over. We present a distributed and decentralized algorithm that computes the mass properties of the robot. Additionally, each module also computes the mass properties of the modules that are directly or indirectly connected to each of its connectors. With this information, each module can independently steer the center of mass towards a desired position by adjusting its joint positions. We present simulation results that show the feasibility of the approach.